(untitled) (Eurasian Journal of Philology Science and Education, 2018)
As the process of globalization involves drastic transformations of economies and societies as a whole, its impact on culture and language must not be underestimated as it can be traced in every aspect of life. To analyse better whether or not the increasinguse of English is detrimental to Kazakh language and culture in the long run, a further and detailed research needs to be conducted on the extent of the use of English in Kazakh society and its effects on Kazakh educational system and culture. In the process of globalization Language borrowings are a clear evidence of linguistic dominance of one language over others; Borrowing has been defined as the introduction of phonological, morphological, lexical, and syntactic items from one language or into another. Also, having noted that the spread of English is an indication of globalization process, the analysis of who supports and who opposes to the spread of English in culture in general and in education in specific, one can draw some conclusions who supports and who rejects globalization.